A meta-analysis of factors predicting parental mediation of children's media use based on studies published between 1992–2019 - Wang, Min (2023)
Restrictive and active parental mediation are widely used to manage child’s media use. Restrictive mediation included limiting child’s media using time/amount, or forbidden media contents. Active mediation refers to discussing media content or use method with their children. While predictors of parental mediation have been broadly studied, conflicting results have been reported. This study aims to examine the predictors of restrictive and active mediation using a meta-analysis of 32 empirical studies and 33 independent sample sets, representing over 21,000 participants. Results show that parents’ negative attitude towards media (r = 0.161) was the main predictor of restrictive mediation, while parents’ involvement (r = 0.156) was the major predictor of active mediation. Video games (r = −0.243) were found to have a stronger effect on the relationship between children’s age and restrictive mediation than any other medium. Also, adolescents (r = 0.230) have a stronger effect on the relationship between parents’ involvement and active mediation. Results further showed that compared to Asia, US (r = 0.129) and Europe (r = 0.102) have stronger effects on the relationship between parents’ negative attitude towards media and active mediation (r = −0.030). Likewise, compared to demographic variables, parents’ involvement and attitude towards media are stronger predictors of parental mediation. Further research should focus on parental mediation on new media and in cross-cultural contexts.